2016
DOI: 10.1161/jaha.115.002787
|View full text |Cite
|
Sign up to set email alerts
|

Dairy Consumption and Risk of Stroke: A Systematic Review and Updated Dose–Response Meta‐Analysis of Prospective Cohort Studies

Abstract: BackgroundA higher milk consumption may be associated with a lower stroke risk. We conducted a comprehensive systematic review and dose–response meta‐analysis of milk and other dairy products in relation to stroke risk.Methods and ResultsThrough a systematic literature search, prospective cohort studies of dairy foods and incident stroke in stroke‐free adults were identified. Random‐effects meta‐analyses with summarized dose–response data were performed, taking into account sources of heterogeneity, and spline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
83
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(103 citation statements)
references
References 45 publications
(228 reference statements)
8
83
0
5
Order By: Relevance
“…This is consistent with a previous meta-analysis by Hu et al (39) showing a non-linear dose–response relationship between milk intake and risk of stroke, with the highest risk reduction of 7–8% with a milk intake of 200–300 ml/day. Also, the meta-analyses by Hu et al (39) and de Goede et al (40) both showed an inverse association between cheese intake and stroke, however only borderline significant in the latter. Accordingly, another meta-analysis on dairy and cardiovascular disease found that intake of cheese and milk as well as yoghurt was inversely associated with cardiovascular disease risk (41).…”
Section: Cardiovascular Diseasementioning
confidence: 95%
“…This is consistent with a previous meta-analysis by Hu et al (39) showing a non-linear dose–response relationship between milk intake and risk of stroke, with the highest risk reduction of 7–8% with a milk intake of 200–300 ml/day. Also, the meta-analyses by Hu et al (39) and de Goede et al (40) both showed an inverse association between cheese intake and stroke, however only borderline significant in the latter. Accordingly, another meta-analysis on dairy and cardiovascular disease found that intake of cheese and milk as well as yoghurt was inversely associated with cardiovascular disease risk (41).…”
Section: Cardiovascular Diseasementioning
confidence: 95%
“…The associations of milk or dairy intake and chronic diseases have been under investigation, but the results are not conclusive. Previous studies reported that milk intake was inconsistently associated high blood pressure, type II diabetes, cardiovascular disease (CVD), and mortality [7,8,9,10,11,12]. …”
Section: Introductionmentioning
confidence: 99%
“…Én metaanalyse undersøkte kun sammenhenger mellom meieriprodukter og total dødelighet 171 . To metaanalyser undersøkte kun sammenhenger mellom meieriprodukter og risiko for hjerneslag 172,173 . Én metaanalyse omhandlet kun ost 174 mens én metaanalyse omhandlet kun melk og syrnede melkeprodukter (inkl.…”
Section: Meieriprodukter Og Risiko For Hjerte-og Karsykdomunclassified
“…Fire metaanalyser fant at spesifikt magre meieriprodukter og/eller mager melk var forbundet med lavere risiko 172,173,176,177 . Alexander og medarbeidere og de Goede og medarbeidere fant at også fete meieriprodukter var forbundet med lavere risiko, men de Goede fant samtidig at helmelk var forbundet med økt risiko 172 . Qin fant ingen signifikant sammenheng mellom fete meieriprodukter og risiko for hjerneslag.…”
Section: Tabell 21 Sammenhenger Mellom Meieriprodukter Og Hjerte-og Kunclassified
See 1 more Smart Citation